Pemanfaatan Komersial Gamelan pada Platform Digital dalam Perspektif Hak Kekayaan Intelektual - Hadi Nur Ikhwan; Nuzulia Kumala Sari; Ermanto Fahamsyah (Jurnal Riset Multidisiplin Edukasi, 2026)
The rapid development of digital technology has facilitated the utilization of various forms of traditional culture on digital platforms, including gamelan as one of Indonesia’s cultural heritages. The use of gamelan on digital platforms, such as social media, streaming services, and audiovisual content, serves not only as a means of cultural preservation but also as a source of economic value through commercial activities. This phenomenon raises legal issues concerning the protection of gamelan as a Traditional Cultural Expression within the framework of Intellectual Property Rights. This study aims to analyze the legal status of gamelan as a Traditional Cultural Expression in Indonesia, the forms of its commercial utilization on digital platforms, and the legal protection available for such utilization. This study employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The findings indicate that gamelan is recognized as a Traditional Cultural Expression protected under Indonesian copyright law. Nevertheless, the increasing use of digital platforms poses challenges to the effective implementation of such protection, particularly with regard to commercial utilization and the management of economic benefits. Therefore, strengthening legal protection mechanisms is necessary to ensure both the preservation and fair utilization of gamelan in the digital era.